DETERMINAN PROPORSI DANA TABARRU’ PADA ASURANSI JIWA SYARIAH DI INDONESIA - Pratama, Muhammad Rasyid Ridha; Suprayogi, Noven (Universitas Airlangga, 2020)
Sharia insurance must separate fund between participant fund and company fund which is effect separate from begining. The purpose of this research is to analyze the determinants of proportion tabarru?fund on participants contribution on sharia life insurance. Focus of research in Indonesia with quantitative approach which data collected from 15 sharia life insurance companys financial statements among 2014 until 2018. Method of research uses regression panel data with fixed effect model. Finding from this research are claim, sharia reinsurance, and operational expenses have significant effect and then investment return of tabarru fund, tabarru? funds growth, rbc and roe have not significant effect. Finding from this research can be implicated for develop sharia life insurance in Indonesia.Keywords: Proportion of Tabarru? Fund, Contribution, Sharia Life Insurance, Split Fund